Enhanced Performance and Stability of Fully Printed Perovskite Solar Cells and Modules by Ternary Additives under High Humidity - Srisamran N. (2023)
To scale up from perovskite solar cells (PSCs) to perovskite solar modules (PSMs), a printing technique with an economical, uncomplicated fabrication process is required to meet the industrial market requirements. Equally important are the high photovoltaic (PV) performance and long-term device stability needed for successful commercialization of the technology. In this study, the effect of ternary additives consisting of guanidinium thiocyanate (GT), thiourea (TU), and urea (U) in MAPbI3 films on power conversion efficiency (PCE) as well as device stability was investigated for the first time based on the experimental results. GT helped influence perovskite crystal grain enlargement, while TU facilitated the perovskite crystal growth, leading to an increase in the current density. Moreover, the use of U was found to reduce the loss in open-circuit voltage as well as the hysteresis of PSC devices. An optimal composition of the ternary additives (1:1:2 molar ratio of GT, TU, and U) resulted in the outstanding performance of fully printed PSCs, showing a PCE of 16.40%, which was significantly higher than that of the pristine device (8.01%). In addition, the unencapsulated device prepared using the ternary additives showed great stability over 1000 h with a PCE retention of 100%, while the PCE of the unencapsulated pristine device decreased by 41.79%. For the large-scale PSM, the ternary additives yielded a significant enhancement of 11.60% PCE, which was over 3 times higher than that for the PSM without additives, as well as 100% retention after 2000 h of both desiccator and ambient storage.